Epidermolysis Bullosa Acquisita in a patient with End Stage Renal Disease: Case study - Umar, Rana Muhammad; Azhar Ali Khan; Waqar Ahmad (Journal of the Pakistan Medical Association, 2023)
Epidermolysis Bullosa Acquisita (EBA) is a rare disorder characterised by sub- epithelial mucocutaneous blistering. Its presentation may be in the form of inflammatory bullous eruption or non-inflammatory tense bullae, milia, and scarring. EBA is an immune disorder mediated with antibodies against type VII collagen, which is a major component of basement membrane zones of the skin and mucosa. Adults are more commonly affected; however, a few paediatric cases have also been reported. Risk factors for its development are still under study. Very few cases are seen of EBA in patients with End Stage Renal Disease and its association with this chronic illness is still under study. This case report presents the case of a patient whose lesions were initially misinterpreted for Calciphylaxis, but histological diagnosis revealed inflammatory EBA. Keywords: Epidermolysis bullosa acquisita, End stage renal disease, Inflammatory bullous eruption.